Menjaga Loyalitas di Era Digital: Peran Pemasaran dan Pengalaman Pengguna di Platform E-Commerce - Ayuningtyas, Farah Noor (Journal of Business and Economics Research (JBE), 2024)
This study aims to analyze the impact of digital marketing on customer loyalty on e-commerce platforms, considering the role of user experience (UX) as a mediating variable. A quantitative approach was applied in this research, with data collected through a survey of 300 respondents who are active users of e-commerce platforms. The main variables measured include digital marketing (content marketing, influencer marketing, and social media advertising), user experience, and customer loyalty. Data were analyzed using Structural Equation Modeling (SEM) to understand the direct and indirect effects between variables. The results show that digital marketing has a significant impact on customer loyalty, both directly and through user experience as a mediator. Effective digital marketing, combined with a positive user experience, was shown to enhance customer engagement and loyalty. These findings highlight the importance of digital marketing strategies that prioritize UX to retain customers on e-commerce platforms. This study provides recommendations for e-commerce companies to focus on UX optimization and the use of relevant digital marketing strategies to strengthen customer loyalty.